Ответы и объяснения

  • Keelat
  • светило науки
2013-05-31T14:53:34+00:00

а) cos13x + cos3x - cos13x = 0

cos3x = 0

3x = пn

x = пn/3

б) sin2x * cos3п/2 + sin3п/2 * cos2x - sinп/2 * cos2x + cosп/2 * sin2x = - корень из 2

sin2x - cos2x = - корень из 2

корень из 2 * (корень из 2 на 2 * sin2x -  корень из 2 на 2 * cos2x) = - корень из 2

sin(2x - п/4) = -1

2x - п/4 = -п/2 + 2пn

2x = -п/4 + 2пn

x = -п/8 + пn

в) 4sinx * cosx * cos2x = 1

2sin2x * cos2x = 1

sin4x = 1

4x = п/2 + 2пn

x = п/8 + пn/2

г) tg x > корня из 3

x = п/3 + пn